Alterações estruturais dos dúctulos eferentes de galos domésticos (Gallus gallus domesticus) acometidos pela Litíase Epididimária - Irina Geraldo (2005)
Epididymary lithiasis (EL) was studied using light and electronic microscopy histopathology in roosters (Gallus gallus domesticus) naturally affected by EL in Minas Gerais, Brazil. EL has beendescribed in the United States and Brazil as a cause of low fertility of male chickens, although the actual primary etiology is as yet unknown. Industrial and free-range chickens were studied and all animals presented some degree of alteration in the eferent ductules (ED), although normal areas were seen alongside variedly altered areas which did not correlate with the presence of luminal stones. ED epithelium non-ciliated cells presented several and large lysosomes. Plicae loss and basal vacuoles were observed in the epithelium of ED dilated regions. Ciliated cells cilia loss and apical cytoplasmic membrane rupture resulted in leak of the cytoplasmic contents to the ED lumen, and ED epithelium desquamation loss occurred with or without lesion to the basal membrane. Basal membrane alterations were associated to profound subepithelial connective tissue damage. Aggregations ofdesquamated epithelium and spermatozoa were seen in the lumen of ED and compact aggregates were considered the basis for calculi formation. The widespread occurrence and high severity of EL lesions are indicative of the importance of EL as a cause of infertility in male chickens